Applicability of reflectance to determine compost maturity - Hunyadi, Gergely; Bíró, Györgyi; Tamás, János (Acta Agraria Debreceniensis, 2012)
The utilisation of composts depends on their maturity and stability. A great part of the determination methods can be set in laboratory and needs complicated sample preparation. The aim of this paper was introduce an effective and fast method which based on the different reflectance of the different organic compounds.During our research we examined the degradation process of compost prisms based on sewage sludge, wood-clipping and straw with temperature and reflectance measurements.As a result, we came to the conclusion that the reflectance, measured at 645 nm or higher, is applicable to determine compost maturity if it is used with temperature measurements.